2018
DOI: 10.15621/ijphy/2018/v5i3/173931
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Electromagnetic Stimulation can Reduce Spasticity in Post-Stroke Patients

Abstract: Background: Level of spasticity in post-stroke patients allow for the predictability of the patient's level of recovery. The study aimed to assess the anti-spastic effect of high-intensity electromagnetic field stimulation in post-stroke condition.Methods: 30 post-stroke patients, randomized into two groups participated. The treatment group (TG) was delivered ten therapies to spastic muscles with high-intensity electromagnetic stimulation. The control group (CG) was delivered ten electrotherapy sessions in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…In patients presenting spasticity after stroke, a study published in 2018 demonstrated the effectiveness of the Super Inductive System in reducing spastic muscle tone and in improving patient function while maintaining results, and even escalating them in a favourable sense of patient evolution, 1 month after completion of the treatment. In this study, the therapy was first applied to the agonist muscles for post-facilitatory inhibition, and later to the weak antagonistic muscles, in order to increase the tone of these muscles, a methodology similar to our study [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients presenting spasticity after stroke, a study published in 2018 demonstrated the effectiveness of the Super Inductive System in reducing spastic muscle tone and in improving patient function while maintaining results, and even escalating them in a favourable sense of patient evolution, 1 month after completion of the treatment. In this study, the therapy was first applied to the agonist muscles for post-facilitatory inhibition, and later to the weak antagonistic muscles, in order to increase the tone of these muscles, a methodology similar to our study [9].…”
Section: Discussionmentioning
confidence: 99%
“…High-intensity electromagnetic stimulation can improve the functionality of poststroke patients, the principle of action being based on the induction of an electromagnetic field that interacts with human body tissues, including myoarthrokinetic tissue, subsequently giving rise to electric currents to reduce spasticity. High-intensity electromagnetic stimulation (Super Inductive System) determines the depolarization of neuronal cells, generating therapeutic effects such as: analgesia, myostimulation, and trophic, resorptive, and elasticizing effects [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Prouza et al identified a 66% reduction in Modified Ashworth Scale and 81% improvement in Barthel Index in patients with post-stroke hemiparesis with rPMS. 12 Stuppler et al studied the effect of rPMS applied on the extensor indices proprius muscle of stroke patients. 13 They suggested that rPMS reduced the spasticity in the finger flexor muscles and facilitated smooth contraction of index finger extensor muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Once the database searches were completed, by combining the different key words, a total of 521 documents were obtained, of which 10 studies were finally included in the systematic review [32][33][34][35][36][37][38][39][40][41]. Figure 1 shows the flow chart of the search process.…”
Section: Selection Of Studiesmentioning
confidence: 99%